Lesões oculares e orais causadas por Tacinga inamoena em ovinos e caprinos - Pequeno, Walter Henrique Cruz (2021)
In the Northeast region of Brazil, ruminants are reared in a variety of ways, and can be seen from intensive to ultra-extensive rearing systems, without any technology and highly dependent on the Caatinga as a source of food, including cacti. In areas of caatinga, which have undergone a degradation process, there is a predominance of certain species of plants, including some that have deleterious effects on animals. Currently, in the Northeast of Brazil, it has been observed that some areas are being invaded by cacti, and problems associated with these species are beginning to be identified. In this dissertation two outbreaks of traumatic injuries associated with grazing and ingestion of Tacinga inamoena by goats and sheep in the state of Paraíba, Brazil, are presented. In the first outbreak, it was observed during a preliminary inspection of the herd that 15 of the 70 animals had ocular changes, the animals were subjected to general physical examination and ophthalmic examination. Excessive tearing, blepharitis, photophobia, corneal opacity, hyphema, corneal neovascularization, corneal ulcers and gloquids adhered to the bulbar conjunctiva and the cornea were the clinical findings identified. The plant was present in several areas and in large quantities in grazing areas, where animals were seen ingesting its fruits. In the second outbreak, two sheep from a total of 100 animals were identified with oral lesions associated with grazing in areas of the plant. One of them was referred to the Veterinary Hospital. On physical examination, the animal showed apathy, anorexia, body score 1.5 in the fur it was possible to identify gloquids. In the oral cavity, halitosis, severe sialorrhea, extensive hemorrhagic ulcers and painful tenderness on palpation were observed. Due to the unfavorable prognosis, he was euthanized. At necropsy, multifocal to coalescent plaques, elevated, firm and with an irregular, ulcerated surface, sometimes crusty, with a yellow to light brown center and erythematous edges were present on the upper and lower lips, oral mucosa, tongue, hard and soft palates. The plant is responsible for causing serious injuries to small ruminants in the Northeast semiarid as well as large economic losses, this problem can still reach wide proportions, since the plant can have invasive behavior, especially in areas where signs of degradation can be identified.